2005
DOI: 10.1002/jcb.20511
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Ca2+ and the Ca2+‐sensing receptor (CASR) in the expression of inducible NOS (nitric oxide synthase)‐2 and its BH4 (tetrahydrobiopterin)‐dependent activation in cytokine‐stimulated adult human astrocytes

Abstract: Since NO production by NOS-2 made by astrocytes activated by proinflammatory cytokines contributes to the killing of neurons in variously damaged human brains, knowing the mechanisms responsible for NOS-2 expression should contribute to developing effective therapeutics. The expression and activation of NOS-2 in normal adult human cerebral cortical astrocytes treated with three proinflammatory cytokines, IL-1beta, TNF-alpha, and IFN-gamma, are driven by two separable mechanisms. NOS-2 expression requires a bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 53 publications
3
52
0
Order By: Relevance
“…In the present work, CaSR expression in the oligodendrocytes is in agreement with previous data (Ferry et al, 2000), whereas the absence of CaSR in astrocytes and microglia is not (Chattopadhyay et al, 1999. It is noteworthy that although in an earlier study failed to detect expression of the CaSR in primary culture of astrocytes isolated from rat brain, later these and others authors demonstrated the presence of CaSR mRNA and protein in primary human astrocytes Dal Pra et al, 2005). The function of the CaSR in normal oligodendroglial cells is currently unknown, but it is reasonable to hypothesize a role in sensing and regulating local ionic homeostasy during neuronal activity.…”
Section: Discussionsupporting
confidence: 92%
“…In the present work, CaSR expression in the oligodendrocytes is in agreement with previous data (Ferry et al, 2000), whereas the absence of CaSR in astrocytes and microglia is not (Chattopadhyay et al, 1999. It is noteworthy that although in an earlier study failed to detect expression of the CaSR in primary culture of astrocytes isolated from rat brain, later these and others authors demonstrated the presence of CaSR mRNA and protein in primary human astrocytes Dal Pra et al, 2005). The function of the CaSR in normal oligodendroglial cells is currently unknown, but it is reasonable to hypothesize a role in sensing and regulating local ionic homeostasy during neuronal activity.…”
Section: Discussionsupporting
confidence: 92%
“…Disruption of Ca 2ϩ homeostasis might be one of the principal mechanisms by which IL-1␤ manifests its neurotoxicity. Indeed, there have been several reports (11,36) showing that Ca 2ϩ disregulation plays an important role in the production of IL-1␤ and nitric oxide synthase in cytokine-stimulated astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…55 The CaR was shown previously to stimulate NO production in other cells. 56,57 The CaR was also found in VSMCs from the gerbilline spiral modiolar artery, 58 from rat aorta, 7 and from human aorta. 59 However, it should be noted that some investigators have been unable to demonstrate the presence of the CaR in aortic VSMCs.…”
Section: Expression Of the Car In The Cardiovascular Tissuesmentioning
confidence: 93%